Stress distribution of two commercial dental implant systems: A three-dimensional finite element analysis - Hao-Sheng Chang; Yi-Chin Chen; Yao-Dung Hsieh; Ming-Lun Hsu (Elsevier, 2013)
Background/purpose: This study investigates the stress distributions in an implant, abutment, and crown restoration with different implant systems, in various bone qualities, and with different loading protocols using a three-dimensional finite element model. Materials and methods: Eight three-dimensional finite element models with 16 test conditions containing four types of dental implants embedded in two different bone qualities (types II and IV) under 100-N axial and 30° oblique loading forces were applied to analyze the stress distribution in the crown restoration, abutment, abutment screw, implant, and supporting bone. Results: The highest maximum von Mises stress was noted in the abutment of a tissue-level implant with the Straumann system (1203.04 MPa) under a 30° oblique loading force. With axial load application, stresses in the screw and abutment of the NobelBiocare system were greater in the tissue-level implant (MK III) than in the bone-level implant (Active). The von Mises stresses in the cortical bone were mostly greater in the tissue-level implant (MK III) than in the bone-level implant (Active) of the NobelBiocare system. However, von Mises stresses in cancellous bone were mostly greater in the bone-level implant (Active) than in the tissue-level implant (MK III) of the NobelBiocare system. Conclusion: Within the limitations of the present study, the Straumann system produced greater stresses than the NobelBiocare system in type IV cortical bone, but they were almost equal in type II bone. By contrast, the NobelBiocare system produced greater stresses than the Straumann system in cancellous bone, regardless of the type of loading angle or bone quality.